THE INFLUENCE OF SERVICE QUALITY, PRICE DISCOUNTS, AND APPLICATION USABILITY ON SHOPEEFOOD CUSTOMER SATISFACTION IN SURABAYA - Ramadhan, Shofia; Lestariningsih, Marsudi (jfpublisher, 2025)
This study examines the influence of service quality, price discounts, and application usability on customer satisfaction among ShopeeFood users in Surabaya. In the contemporary digital era, application-based food delivery services have experienced substantial growth, with ShopeeFood competing alongside numerous similar platforms in an increasingly saturated market. Understanding the determinants of customer satisfaction has become critical for maintaining competitive advantage in this sector. This research employed a quantitative approach utilizing a survey method. Primary data were collected through structured questionnaires distributed via Google Forms to 75 respondents who were identified as regular ShopeeFood users in Surabaya. The data were analyzed using multiple linear regression analysis with SPSS version 26. The findings reveal that service quality does not exert a significant influence on customer satisfaction. Conversely, both price discounts and application usability demonstrate significant positive effects on customer satisfaction. These results indicate that ShopeeFood customers prioritize promotional pricing strategies and user-friendly application interfaces when selecting food delivery services. The study contributes to the understanding of consumer behavior in digital food delivery platforms and provides practical implications for service providers seeking to enhance customer retention through targeted strategic interventions.